Veterans Health Administration's MOVE! Weight Management Program: Primary Care Clinicians' Perceptions of Program Implementation. Issue 10 (1st October 2015) - Arigo, Danielle; Funderburk, Jennifer; Hooker, Stephanie; Dundon, Margaret; Evans-Hudnall, Gina; Dubbert, Patricia; Dickinson, Eva-Maria; Catanese, Sarah; O'Donohue, Jenny
ABSTRACT: The Veterans Health Administration's MOVE! Program is the largest health care-delivered weight loss intervention in the United States. As a referring clinician's perceptions and knowledge of health programs may impact implementation, examining perceptions of MOVE! may inform improvements to this and other programs. This study investigated primary care clinician perceptions of MOVE! ( n = 754, 50% nurses). Perceived effectiveness ratings were highest for groups with 11 to 25 group members ( p < 0.01) and for a combined lecture and support group format ( p = 0.026), though session length and several other aspects of delivery were not associated with perceptions of effectiveness. MOVE! staff also rated the program as more effective than did other clinicians ( p < 0.01). Many respondents lacked knowledge about program specifics, especially those not involved with MOVE! delivery (vs. those directly involved; p < 0.01). These findings indicate that variety in group size and format is related to perceptions of MOVE! effectiveness. Also, clinicians not involved with MOVE! may lack knowledge about the program and underestimate its effectiveness, which could negatively affect referral likelihood or enthusiasm expressed to referred patients. Findings highlight opportunities for clarifying perceptions of a weight control program among clinicians in a large health care system.